Factors influencing condominium purchase intention in Phnom Penh, Cambodia - Sok, Chhoyyi; Soun, Hong (Faculty of Business and Economics, University of Surabaya, 2026)
The rapid urbanization and economic growth in Phnom Penh, Cambodia, have significantly transformed the real estate landscape, particularly in the condominium sector. Hence, it is the reason to study “Factors influencing condominium purchase intention in Phnom Penh, Cambodia”. This paper structured into five chapters. Firstly, it introduces the study, establishes the statement of problem, research questions, objectives, scope, significance, and layout of study. The research questions are: “What are the main challenges faced by condominium developers in Cambodia?”, and “What factors influence condominium purchase intention in Phnom Penh, Cambodia?”. Therefore, the researcher has set two objectives for the study: (1) To understand the main challenges faced by condominium developers in Cambodia, and (2) To identify and analyze the key factors influence condominium purchase intention in Phnom Penh, Cambodia. Secondly, it critically reviews the relevant literature, synthesizing existing knowledge and identifying the theoretical foundation and research gap the study addresses. After that, it justifies the chosen research design, data collection methods, sampling strategy, and analytical techniques. The research utilized a qualitative and quantitative approach, collecting data from 385 respondents through a structured questionnaire. Statistical analysis was conducted using SPSS to examine the impact of six key factors: Perceived value, Quality of life, Brand trustworthiness, Social influence, Design, and Promotion. Then, the findings indicate that Perceived value, Quality of life, Brand trustworthiness, and Social influence highlight their significant influences on the purchase intention. Additionally, Design and Promotion were found to have a partial impact. Finally, by addressing these critical factors, condominium developers can improve the condominium experiences for consumers. Keywords: Perceived Value, Quality of Life, Brand Trustworthiness, Social Influence, Design, Promotion